Determinación de las cantidades de los RSU potencialmente reciclables que recogen los minadores en Riobamba - Chucuri Caranqui, Nataly Estefania (2025)
The objective of this research was to determine the quantity and type of potentially recyclable municipal solid waste (MSW) collected by informal waste pickers—known as miners—in the city of Riobamba. Using a mixed-method approach and a non-experimental design, surveys, interviews, and direct observations were conducted with informal recyclers, identifying a total of 37 active miners, both Ecuadorian and Venezuelan nationality. These individuals collect approximately 3121.41 kg of recyclable materials per day, representing only 5.46% of the total waste generated in the city (around 57,168 kg/day), which is then sold to the 17 recycling centers currently operating in Riobamba. The results reveal a low efficiency in waste recovery, mainly due to inadequate infrastructure, limited source separation, and the informal nature of the recycling sector. Additionally, income disparities were observed among miners based on nationality, type of material collected, and area of operation, highlighting the importance of mobility and access to higher-value materials such as copper and aluminum. These findings underscore the need to incorporate miners into comprehensive waste management plans in order to enhance recycling efficiency and promote a culture of waste separation at the source.